Insect Diversity of Mangrove Ecosystems in Beras Basah Village, Langkat, North Sumatra, Indonesia - Siregar, Ameilia Zuliyanti; Joshi, Ravindra C.; Basyuni, Mohammad; Priawandiputra, Windra; Hasanuddin, Aam; Sim, Yenti (Department of Agronomy and Horticulture, IPB University, 2025)
This study aimed to investigate the diversity of insects, including stingless bees (Heterotrigona) in the mangrove ecosystem of Beras Basah Village, Langkat Regency, North Sumatra, Indonesia. The mangrove plantation in Beras Basah Village contained 11 species, including Rhizophora apiculata, Rhizophora mucronata, Rhizophora. stylosa, Avicennia marina, Sonneratia alba, Bruguiera gymnorhizza, Xylocarpus granatum, Excoecaria agallocha, Scyphiphora hydrophyllacea, Lumnitzera racemosa, and Nypa fruticans. Additionally, five flowering plant species were identified in the vicinity: Antigonon leptopus, Asclepias curassavica, Helianthus annuus, Calliandra grandiflora, Portulaca grandiflora. Other plant species recorded in the area included Cocos nucifera, Pandanus amaryllifolius, Leucaena leucocephala, Ziziphus mauritiana, Albizia chinensis, and Terminalia catappa. Insect identification from four observations using sweep nets, yellow sticky traps, and blue pan traps resulted in the collection of 1,525 individual insects belonging to eight orders, 17 families, and 19 genera. These insects included ten predators and pests, comprising five Odonata species (Neurothemis terminata, Orthetrum sabina, Orthetrum testaceum, Potamarcha congener, Zyxomma obtusum) and five ant species (Camponotus spp., Crematogaster spp., Nylanderia spp., Odontoponera denticulate, Pheidole spp.). The insect functional status within the mangrove area was determined to include seven species of scavengers, 12 species of herbivores, two species of pollinators, 19 species of predators, one species of parasitoid, and four species of insect disease vectors. This study provides valuable insights into the insect diversity and ecological roles within the mangrove ecosystem of Beras Basah Village, contributing to a better understanding of the conservation and management of this important habitat.